Protective Effect of Commercial Grade Vitamin C against Alcohol-induced Testicular Damage in Male Wistar Rats - Taiwo Emmanuel George; Peter Okhemukhokho Okhiai; Ifabunmi Oduyemi Osonuga; Olusoji Adebusoye Oyesola (Journal of Human Reproductive Sciences)
Background: Alcohol consumption has a negative effect on male fertility, but Vitamin C may be able to alleviate this effect. Aims: In this study, the protective effect of Vitamin C against alcohol-induced testicular damage in adult male Wistar rats was evaluated. Settings and Design: This study was conducted in a University setting. Following a 14-day acclimatisation period, forty adult male Wistar rats were randomly divided into eight groups of five rats. The control group received only food and water, test group B received alcohol only, test group C to E received different doses of Vitamin C, test group F to G received different doses of Vitamin C and alcohol. Materials and Methods: After a 21-day treatment period, the testis were harvested and analysed for sperm parameters, antioxidant enzyme activity, level of lipid peroxidation and histopathological changes. Statistical Analysis Used: All analyses was performed using SPSS (version 16) and Microsoft Excel (2019) using Student's t-test. Results: The results showed that in groups administered with alcohol only, there was a decrease in sperm count. Sperm motility, morphology, viability and antioxidant enzyme activity, but increase in the level of lipid peroxidation. In groups treated with Vitamin C and alcohol, there was improvement in the sperm parameters, antioxidant enzymes activity and a decrease and decrease in lipid peroxidation. Furthermore, in the histology of the testis, regenerative changes were seen. Conclusion: The chronic consumption of alcohol can have a deleterious effect on the testis, but commercial-grade Vitamin C can reverse these effects.